EFFICIENCY OF SOME CLASSIFICATION METHODS ADOPTED IN CLINICAL REMINDER SYSTEMS IN CASES OF MIXED DATA - Imad H.A. AL-Iathary; Murtadhah M.H (مجلة جامعة الانبار للعلوم الصرفة, 2008)
Cluster analysis techniques are widely used in medical researches. Clustering techniques are not unique and hence users must be extremely conscious about what to use in order to analyze their data. The choice of unsuitable technique will resulted directly in a misleading output that cannot be interpreted or even give hints for further investigations.Understanding data variability by the use of inferential methods will help us adopt the most appropriate classification technique and accordingly enhance both building more robust CRS and CDSS's.